Nucleic acid-sensing toll-like receptors: Important players in Sjögren’s syndrome - Alexopoulou, Lena (Frontiers in Immunology, 2022)
Sjögren’s syndrome (SS) is a chronic systemic autoimmune disease that affects the salivary and lacrimal glands, as well as other organ systems like the lungs, kidneys and nervous system. SS can occur alone or in combination with another autoimmune disease, such as systemic lupus erythematosus (SLE) or rheumatoid arthritis. The etiology of SS is unknown but recent studies have revealed the implication of the activation of innate immune receptors, including Toll-like receptors (TLRs), mainly through the detection of endogenous nucleic acids, in the pathogenesis of systemic autoimmune diseases. Studies on SS mouse models suggest that TLRs and especially TLR7 that detects single-stranded RNA of microbial or endogenous origin can drive the development of SS and findings in SS patients corroborate those in mouse models. In this review, we will give an overview of the function and signaling of nucleic acid-sensing TLRs, the interplay of TLR7 with TLR8 and TLR9 in the context of autoimmunity, summarize the evidence for the critical role of TLR7 in the pathogenesis of SS and present a possible connection between SARS-CoV-2 and SS.